Prerada prehrambenih proizvoda u okviru gazdinstva - praksa u Mađarskoj, mogućnosti u Srbiji (Food Product Processing in the Frame of Farming-Practice in Hungary, Opportunities in Serbia) - Hajnalka Kovács Sárkány; Vilmos Kovács (DETUROPE)
Food product processing in the frame of farming in legal aspect does not precisely defined in Serbia. In this study is introduced Hungarian agricultural product processing in registered farms/househols, and then analyzed the legislations in Republic of Serbia related to this issue. As a result of study, the authors recommended some possible steps for regulation of this domain.